The influence range of the biogas desaturation method for mitigating sand liquefaction - Peng, Erxing; Li, Dandan; Hu, Xiaoying; He, Binbin; Dang, Haiming; Liu, Youqian (Frontiers in Earth Science, 2024)
To clarify the influence range and saturation distribution after biogas desaturation method applied, a three-dimensional model is established with TOUGH2 software to analysis the effect of construction parameters, such as grouting volume, grouting rate, grouting depth, nitrogen source concentration and soil porosity. After that, the sensitivity of parameters on influence range is determined. The grouting volume and porosity is the most sensitive to the lateral and vertical influence range, respectively. This study can provide a basis for the engineering practice of treating liquefiable subgrade by the biogas desaturation method.